2002
DOI: 10.1159/000057602
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Asymptomatic Hematuria and/or Proteinuria in Men

Abstract: Aim: To elucidate prognosis and prevalence of chronic renal diseases among proteinuric and/or hematuric subjects found in mass screening, a long-term follow-up study (6.35 years, range 1.03–14.6 years) was conducted on Japanese working men. Methods: A total of 772 subjects selected from 50,501 Japanese men aged 15–62 years were found to have asymptomatic hematuria (n = 404), concomitant hematuria and proteinuria (n = 155), and proteinuria (n = 213) during their annual urine examination and five consecutive uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 14 publications
6
59
2
3
Order By: Relevance
“…This threshold, recommended by the American Urological Association (AUA)-endorsed guidelines in 2012, was lowered from previous recommendations, which used 40 years as the threshold. This was motivated by a review of the literature, which showed that 95 of 98 (97%) patients diagnosed with a urinary tract malignancy in 17 screening studies [7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27] were older than 35 years; and 406 of 409 (99.3%) patients diagnosed with a urinary tract malignancy in the initial and further workup studies were older than 35 years.…”
Section: Discussionmentioning
confidence: 99%
“…This threshold, recommended by the American Urological Association (AUA)-endorsed guidelines in 2012, was lowered from previous recommendations, which used 40 years as the threshold. This was motivated by a review of the literature, which showed that 95 of 98 (97%) patients diagnosed with a urinary tract malignancy in 17 screening studies [7][8][9][10][11][12][17][18][19][20][21][22][23][24][25][26][27] were older than 35 years; and 406 of 409 (99.3%) patients diagnosed with a urinary tract malignancy in the initial and further workup studies were older than 35 years.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, however, demonstrated that the most cost effective frequency for general screening is once every 10 years in asymptomatic individuals (21). Currently, annual health checks are mandatory for employees age 40 years and over in Japan (22).…”
Section: Discussionmentioning
confidence: 99%
“…Without proteinuria, the majority of the patients have early IgAN, with the remainder having thin basement membrane disease, Alport's syndrome, interstitial diseases, papillary necrosis, hypercalciuria, hyperuricosuria, or sickle cell trait/disease. [23][24][25] However, in most centers, a renal biopsy is not warranted unless the result would be useful for screening potential living related kidney donors for genetically determined diseases such as Alport's syndrome, for life insurance and employment purposes, or for providing reassurance to the patient. Although the study by Gutiérrez et al gives clinical reassurance that the long-term prognosis of IgAN with minimal proteinuria is favorable, the true prognosis of patients with isolated microhematuria is not completely elucidated, and the findings that isolated microhematuria is an independent risk factor for ESRD is concerning.…”
mentioning
confidence: 99%
“…12,26 Although some studies have found a high frequency of glomerular disease in patients with isolated microhematuria, the renal biopsy added little to the therapy and clinical management of these patients. [23][24][25] Because some of these patients may later develop hypertension, proteinuria, and/or renal insufficiency, especially those with Asian ancestry, we recommend at least yearly follow-up in any patient with isolated microhematuria to monitor BP, renal function, and the level of proteinuria. We do not recommend a renal biopsy at the time of diagnosis of isolated microhematuria because the studies to date do not show that identifying glomerular disease affects clinical management or therapy.…”
mentioning
confidence: 99%